Sorority among older women in Santiago of Chile: An analysis in the light of feminist gerontology - Gómez-Rubio, Constanza Alejandra (2021)
Recent studies address the relationships between women within self-managed organizations of older people. For this reason, this qualitative research analyzes the discourses of older women inSantiago of Chile, around the relationships they establish between them, within self-managed community organizations, and the relationship they build with their own old age. 18 interviews were conducted with older women between 2016 and 2019, which were analyzed through critical discourse analysis. The results referred to three topics: the relevance of the collective in female old age, the practices of resistance against the control of the Church and the State, and the fact of being old women. The discourse of mutual support and sisterhood are keys to understanding their relationships. The importance of producing female role models of old age, serving the younger generations of women, is highlighted.